Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.1111/jan.15824
|View full text |Cite
|
Sign up to set email alerts
|

How is complexity measured and detected among community dwelling older people aged 65 years and over? A scoping review

Abstract: AimTo identify and explore tools that measured and detected complexity of care among community dwelling people aged 65 years and older.Data SourcesDatabases were searched for articles published up to 23 September 2022 including CINAHL, EMBASE and MEDLINE, Cochrane database for trials and grey literature.MethodsA scoping review was conducted and reported in accordance with the PRISMA guidelines. Eligible articles included those with participants aged over 65 years, living in the community and studies that inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…In community nursing services around the world there are various assessment processes and tools, but their efficacy has not been comprehensively examined (Boak et al, 2023;Lyndon et al, 2021). The role of the community nurse goes beyond the immediate needs of the client and includes with consideration of meeting the broader healthcare needs (Lyndon et al, 2021), which can be strengthened by adopting a systematic, objective assessment approach.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In community nursing services around the world there are various assessment processes and tools, but their efficacy has not been comprehensively examined (Boak et al, 2023;Lyndon et al, 2021). The role of the community nurse goes beyond the immediate needs of the client and includes with consideration of meeting the broader healthcare needs (Lyndon et al, 2021), which can be strengthened by adopting a systematic, objective assessment approach.…”
Section: Discussionmentioning
confidence: 99%
“…We conducted a scoping review to explore complexity of care of older people and how complexity of care was detected. The review demonstrated there are limited studies on the detection of the complexity of care, even though there was reference to the need to explore the concept further (Boak et al, 2023). The review found two comprehensive tools for objectively measuring complexity.…”
Section: The Role Of Community Nursesmentioning
confidence: 99%
See 1 more Smart Citation